Perubahan Sifat Kimia Tanah Sawah Saat Serapan Hara Maksimum Oleh Padi (Oryza sativa L.) Setelah Aplikasi Campuran Kompos Tandan Kosong Kelapa Sawit (TKKS) Dengan Abu Boiler - Maryati '; Nelvia '; Edison Anom (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research analyses the changes of the chemical character of rice field soil when the maximum nutrient uptake by the rice after the application of mixture oil palm empty bunches compost with boiler ash. This research was implemented Kacamatan Kampar Timur, Kabupaten Kampar and started in Desember 2012-July 2013. The chemical character of the soil was analysis in soil research center in Bogor.Completely randomized design which consists of four treatments. 1) F0 (without compost TKKS and boiler ash) 2) F1 (5 tons of compost TKKS/ha+500 kg of boiler ash/ha) 3) F2 (5 tons of compost TKKS/ha+750 kg boiler ash/ha) 4) F3 (5 tons of compost TKKS/ha+1000 kg boiler ash/ha) each treatment was repeated three times and obtained 12 experimental units. For soil chemical character research (pH, C-organik, N-total, C/N, P-Bray 1, K-dd, Ca-dd, Mg-dd, Na-dd, KB dan KTK) just taken 2 repeated that was repeated 1 and 2 for each treatment. Data of saoil chemical character from laboratorium analyses result was represented descriptive way.Generaly the results showed that the application of a mixture oil palm empty bunches compost with boiler ash on the ground tends to improve the chemical properties of rice field soil when the maximum nutrient uptake of paddy (48 days after planting), especially at treatment F2 for the parameters pH, KB, K-dd, Ca-dd and Mg-dd. Keyword: Rice field soil, oil palm empty bunches compost and boiler ash